Purchasing and logistic management: The challenges in coordinating the logistics activities within and among purchaser and the supplier - Lim, Ming Tian; Mohamed Ismail, Risyawati (2013)
Nowadays, logistics management is regarded as a strategy on its own.Logistics in many companies remained a crucial element that could disrupt the operation if unfittingly handled.One of the main problems is the difficulty to measure logistics success.There are also issues in indicating the contribution of logistics to the company and the value-added created by means of logistics.The purpose of this paper is to examine the issues and challenges faced by the purchasers as well as the relevant parties involved in the industry.These issues have been the hindrance for logistics effectiveness in Malaysia. Purchasers faced this problem for a very long period, which will lead to the problem between purchasers and the suppliers. This paper attempts to open up various issues surrounding this complex and fragmented industry. It thus, provided a base for future researchers to examine any aspects of logistics and supply chain management between supplier and purchaser in Malaysia.